Signal processing with frequency and phase shift keying modulation in telecommunications - Juliy Boiko; Volodymyr Tolubko; Oleg Barabash; Oleksander Eromenko; Yevhen Havrylko (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
In this paper represents research improving effectiveness of signal processing in telecommunication devices especially for its part, which relates to providing its noise resistance in conditions of noise and interference. This objective has been achieved through development of methods and means for optimization of filtering devices and semigraphical interpretation of clock synchronization systems in telecommunications with frequency shift keying on the base of stochastic models what determines relevance of the subject. Separately, in an article considered the urgent task is using of modified synchronization methods based on the interference influence of adjacent symbols on the phase criterion tract, in particular the use of the modified synchronization scheme, in order to get a formalized outlook representation of the synchronization schemas based on the polyphase structures with using a bank of filters, that allows to improve the characteristics of digital telecommunication channels. This work is devoted to the examination and modeling of these ways. The proposed ideas and results for the construction of synchronization systems can be used in modern means of telecommunication.